2018
DOI: 10.1007/s00203-018-1535-x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and induction of mechanisms of resistance to stresses related to the inoculation with Azospirillum brasilense

Abstract: We investigated the effects of Azospirillum brasilense strains Ab-V5 and Ab-V6 in the induction of mechanisms of systemic acquired resistance (SAR) and induced system resistance (ISR) on maize (Zea mays L.) plants. Under normal growth conditions, the treatments consisted of the standard inoculation of cells at sowing, and leaf spray of cells or their metabolites at the V2.5 growth stage; under saline stress (170 mM NaCl), the treatment consisted of standard single and co-inoculation of A. brasilense and Rhizob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 59 publications
1
27
0
1
Order By: Relevance
“…Indolacetic acid (IAA) is one of the most important molecules produced by Azospirillum sp. and studies suggest bacterial biosynthesis of IAA can be drastically affected by environmental conditions and exposure to other compounds [16,18]. Thus, the application of IBA may have influenced the production of the rhizobacteria growth-promoting substances.…”
Section: Sources Of Variation Rc (%) Sv (%) Fr (%) S (%) CC (%) Dm (Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Indolacetic acid (IAA) is one of the most important molecules produced by Azospirillum sp. and studies suggest bacterial biosynthesis of IAA can be drastically affected by environmental conditions and exposure to other compounds [16,18]. Thus, the application of IBA may have influenced the production of the rhizobacteria growth-promoting substances.…”
Section: Sources Of Variation Rc (%) Sv (%) Fr (%) S (%) CC (%) Dm (Gmentioning
confidence: 99%
“…Studies have shown promising results for association with the PGPR species Azospirillum brasilense; it promotes root development by increasing the production of hormones, leading to growth and development of plants [16][17][18]. In this context, the objective of this study was to assess the viability of producing blueberry nursery plants from cuttings using different doses of IBA in association with A. brasilense.…”
Section: Introductionmentioning
confidence: 99%
“…These bacteria in association with plants may generate several benefits to the host, such as phytohormone biosynthesis, biological nitrogen fixation (BNF), and induction of resistance mechanisms. Consequently, there are positive effects on the enhancement of root traits, tolerance to abiotic stress, and defense against pathogens [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown promising results for association with the PGPR species Azospirillum brasilense, since it promotes root development by increasing the production of hormones, leading to growth and development of plants [14][15][16]. In this context, the objective of this study was to assess the viability of producing blueberry nursery plants from cuttings using different doses of IBA in association with A. brasilense.…”
Section: Fruit Cropsmentioning
confidence: 99%